The synthesis of benzisothiazole and benzothiazole natural products - Blunt, Christoper Edward (2018)
Chapter 1 gives an introduction to benzisothiazole and benzothiazole natural products. It explores the scope of natural products that are known within these families and discusses what they are used for, how they have been made and how they may have been biosynthesised. Chapter 1 provides a review of each family of natural products in turn. Chapter 2 describes the total synthesis of the benzisothiazole natural products aulosirazole and pronqodine A, and a series of unnatural analogues. The Chapter begins with a short discussion on the use of the Diels-Alder reaction for the formation of naphthoquinones, then illustrates this strategy for the first synthesis of aulosirazole. The chapter continues with the synthesis of pronqodine A, a structurally similar natural product. The Chapter ends with an evaluation of these compounds as inhibitors of indoleamine-2,3-dioxygenase. Chapter 3 contains work towards the synthesis of the benzothiazole containing natural product erythrazole A. The first half of the Chapter focuses on the formation of the heterocyclic core, originally attempting to use a biomimetic strategy but switching to an approach utilising the oxidative cyclisation of thioamides. The second half of the Chapter discusses many routes to synthesise and introduce the terpene derived side chain. Chapter 4 contains experimental detail for the work carried out.